Sexual dimorphism of microglia and synapses during mouse postnatal development - Weinhard, L; Neniskyte, U; Vadisiute, A; Di Bartolomei, G; Aygün, N; Riviere, L; Zonfrillo, F; Dymecki, S; Gross, C (Wiley, 2018)
Microglia participate in synapse remodeling in the cortex and hippocampus during mouse postnatal development. Although sex differences in microglia activity during embryonic development have been reported in these regions, it remains unexplored whether microglia show sexually dimorphic features during the early postnatal period, a critical window for synapse formation and maturation. Here, we investigated morphological and functional features of microglia across early postnatal development as well as morphological features of both pre‐ and postsynaptic neuronal compartments in the mouse hippocampus. We found a sex‐dependent shift in microglia volume and phagocytic capacity across the first four postnatal weeks. Measurements of synaptic features revealed sex differences in the density of synaptic spines and boutons during the second postnatal week. These data are consistent with a precocious development of both microglia and synapses in the female brain. We further hypothesize that this bias may contribute to sex‐specific brain wiring.